PVECM Analysis of RLS, AHH, TPAK in Bangka Belitung Province - Muhammad Farhan; Arfida Boedirochminarni (Jurnal Ekonomi Pembangunan, 2025)
This study was conducted to analyze the impact of average length of schooling and life expectancy on the labor force participation rate in 7 districts/cities in Bangka Belitung province in the short and long term. This is quantitative research. This study employs the PVECM analysis method with panel data from 7 districts/cities in Bangka Belitung province from 2006 to 2023, using Eviews-12 software. The results of the PVECM analysis indicate that the short-term effects of average length of schooling and life expectancy are significantly positive on the labor force participation rate. Then, in the long term, the average length of education and life expectancy also have a significant positive effect on the labor force participation rate.